Anatomy & physiology made incredibly easy! - 4 0 16; Comerford, Karen C.; 5 (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
A reference guide to anatomy and physiology, providing an introduction to the human body, discussing its chemical organization, and featuring an in-depth look at each of twelve body systems, as well as information on nutrition and metabolism, and fluids, electrolytes, acids, and bases. Includes illustrations, memory-joggers, and quizzes.
The human body -- Genetics -- Chemical organization -- Integumentary system -- Musculoskeletal system -- Neurosensory system -- Endocrine system -- Cardiovascular system -- Hematologic system -- Immune system -- Respiratory system -- Gastrointestinal system -- Nutrition and metabolism -- Urinary system -- Fluids, electrolytes, acids, and bases -- Reproductive system -- Reproduction and lactation.
Includes bibliographical references (p. 367) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Human physiology;Human anatomy;Anatomy.;Physiological Processes.;Physiology;Human anatomy -- Outlines, syllabi, etc.;Outlines, syllabi, etc.;Outlines, syllabi, etc.;Outlines, syllabi, etc; 20; 2